Intrascrotal and osseous sarcoidosis mimicking intrascrotal organ cancer and bony metastasis - Nureki, Shin-ichi; Miyazaki, Eishi; Yamasue, Mari; Takenaka, Ryuichi; Ando, Masaru; Kadota, Jun-ichi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
We report a case of sarcoidosis with concomitant epididymis, testes, and phalanxes involvement mimicking intrascrotal organ cancer and metastatic bony disease. A 23-year-old man developed blurred vision and hyperemia of the left eye, and was diagnosed as having left iritis. A chest computed tomography scan detected bilateral hilar lymphadenopathy and lung nodular shadows. A transbronchial lung biopsy revealed a non-caseating granuloma and he was diagnosed with sarcoidosis. One year after the onset of his eye symptoms, he noticed enlargement of his right scrotum. Magnetic resonance imaging detected lesions of the right epididymis, bilateral testes, and bilateral phalanxes. A technetium-99m scintigram revealed a high accumulation in the bilateral bones of extremities. These radiological findings mimicked intrascrotal organ cancer and metastatic bony disease. Pathologic evaluation following the right epididymectomy revealed non-caseating granulomas compatible with sarcoidosis. Three and half years after the appearance of intrascrotal and bony lesions, they improved spontaneously.